Analysis of the Rural-Urban Migration flow in Algeria Using the model of Harris Todaro - KHALED SENATOR; Imadeddine LACHEB (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
This study is a participation to examine the rural-urban migration flows in Algeria using Harris and Todaro model that focus on the economic factors, especially the difference of wages and the job opportunities.